PKM. SMP DWIJENDRA BUALU DALAM PELATIHAN MEMBUAT ALAT PERAGA PADA PEMBELAJARAN MATEMATIKA - Ni Komang Janukariati; Sirilus Ngahe; I Komang Sukendra (Jurnal Pengabdian Kepada Masyarakat Widya Mahadi, 2022)
Mathematics is one of the subjects that children do not like. However, there are still many teachers who have not maximally sought efforts so that such a situation can be reduced or even changed. In the learning process, the teacher should assist students in understanding abstract mathematical objects through observation and the help of learning media in the form of teaching aids. The purpose of this PKM activity is to help teachers make teaching aids that can be used as learning media in learning mathematics. This training activity was held at SMP Dwijendra Bualu for two days, on February 4 and 5, 2022. Steps for implementing the training: planning, conducting workshops, training in making teaching aids, mentoring the practice of using teaching aids, evaluation and reflection. The targets and outcomes are in accordance with the training objectives that have an impact on: (1) teachers are more skilled and creative in making teaching aids and finding creative ways to explain mathematical concepts, (2) learning that is more varied and interesting which ultimately makes it easier for students understand the basic concepts of mathematics